Clinically available immunosuppression averts rejection but not systemic inflammation after porcine islet xenotransplant in cynomolgus macaques. Issue 3 (1st December 2021) - Graham, Melanie L.; Ramachandran, Sabarinathan; Singh, Amar; Moore, Meghan E. G.; Flanagan, E. Brian; Azimzadeh, Agnes; Burlak, Christopher; Mueller, Kate R.; Martins, Kyra; Anazawa, Takayuki; Appakalai, Balamurugan N.; Bansal‐Pakala, Pratima; et al.
Abstract : A safe, efficacious, and clinically applicable immunosuppressive regimen is necessary for islet xenotransplantation to become a viable treatment option for diabetes. We performed intraportal transplants of wild‐type adult porcine islets in 25 streptozotocin‐diabetic cynomolgus monkeys. Islet engraftment was good in 21, partial in 3, and poor in 1 recipient. Median xenograft survival was 25 days with rapamycin and CTLA4Ig immunosuppression. Adding basiliximab induction and maintenance tacrolimus to the base regimen significantly extended median graft survival to 147 days ( p  < .0001), with three animals maintaining insulin‐free xenograft survival for 265, 282, and 288 days. We demonstrate that this regimen suppresses non‐Gal anti‐pig antibody responses, circulating effector memory T cell expansion, effector function, and infiltration of the graft. However, a chronic systemic inflammatory state manifested in the majority of recipients with long‐term graft survival indicated by increased neutrophil to lymphocyte ratio, IL‐6, MCP‐1, CD40, and CRP expression. This suggests that this immunosuppression regimen fails to regulate innate immunity and resulting inflammation is significantly associated with increased incidence and severity of adverse events making this regimen unacceptable for translation. Additional studies are needed to optimize a maintenance regimen for regulating the innate inflammatory response. Abstract : A clinically available immunosuppressive regimen prevents rejection of wild‐type porcine islets in cynomolgus macaques but fails to control xenogeneic systemic inflammation, previously unrecognized in cell transplantation, thereby precluding its direct applicability.